UMPSA, Grab Malaysia sign collaboration to provide flexible education access for gig workers - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2024)
PEKAN, 11 January 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Grab Malaysia strengthened their cooperation by signing a Memorandum of Understanding (MoU) today to provide access to education and training aimed at improving the academic qualifications and competence of gig workers.